(untitled) (Global Journal of Science Frontier Research, 2019)
Genetic variability, heritability and genetic advance study was conducted using 55 hot pepper genotypes with the objectives to identify the extent of genetic variability explained by genotypes and to assess the magnitude of heritability (broad sense) and expected genetic advance. The experiment was conducted during 2016-2018 at three locations in Wolaita, Southern Ethiopia using RCBD with three replications. The result illustrated the existence of sufficient genetic variability in growth, yield and quality characters. The fresh fruit yield ranged from 3151.43kg/ha to 43002.86kg/ha with a difference of 39851.43kg/ha. Similarly, the oleoresin content and dry weight depicted range of 1.44-10.20% and 489.83-7652.85kg/ha, respectively indicating ample variability for further improvement and selection of superior genotype. The PCV in percent ranged from 33.44 (for oleoresin) to 8.50 (branch number) and GCV ranged from 32.15 to 7.21 for same traits which is an indication for broad genetic base and these traits are under the control of additive gene effects and, hence, there is a good scope for further improvement. Heritability (in broad sense) ranged from 60.39 (fruit number) to 92.39 (oleoresin content).